(untitled) - Huỳnh, Tố Uyên (Can Tho, 2009)
This reasearch is to obtain learners perceptions about the new material regarding the adaptation of tasks in pre-writing stage. This study focuses only on descriptive writing. The pre-writing activities are brainstorming, clustering, questioning, and outlining.
Keywords: English language; Writing